Hund’s flat band in a frustrated spinel oxide - Oh, Dongjin; Hampel, Alexander; Wakefield, Joshua P.; Moen, Peter C.; Smit, Steef; Luo, Xiangyu; Zonno, Marta; Gorovikov, Sergey; Leandersson, Mats; Polley, Craig; Kundu, Asish K.; Rajapitamahuni, Anil; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2025)
Electronic flat bands associated with quenched kinetic energy and heavy electron mass have attracted great interest for promoting strong electronic correlations and emergent phenomena such as high-temperature charge fractionalization and superconductivity. Intense experimental and theoretical research has been devoted to establishing the rich nontrivial metallic and heavy fermion phases intertwined with such localized electronic states. Here, we investigate the transition metal oxide spinel LiV2O4, an enigmatic heavy fermion compound lacking localized f orbital states. We use angle-resolved photoemission spectroscopy and dynamical mean-field theory to reveal a kind of correlation-induced flat band with suppressed interatomic electron hopping arising from intra-atomic Hund’s coupling. The appearance of heavy quasiparticles is ascribed to a proximate orbital-selective Mott state characterized by fluctuating local moments as evidenced by complementary magnetotransport measurements. The spectroscopic fingerprints of long-lived quasiparticles and their disappearance with increasing temperature further support the emergence of a high-temperature “bad” metal state observed in transport data. This work resolves a long-standing puzzle on the origin of heavy fermion behavior and unconventional transport in LiV2O4. Simultaneously, it opens a path to achieving flat bands through electronic interactions in d-orbital systems with geometrical frustration, potentially enabling the realization of exotic phases of matter such as the fractionalized Fermi liquids.
Publisher Copyright: Copyright © 2025 the Author(s).
Keywords: flat band; frustrated lattice; heavy fermion transition metal compound; Hund’s coupling